The Application of Collaborative Government in A Case Study of Cooperation to Protect Mangrove Forests in Benoa Bay Bali - Aryadi, Ferdiaz Syahputra; Putra, Muhamad Rassya (Proceedings International Conference on Education Innovation and Social Science, 2024)
The reclamation action carried out by PT Pelindo in Benoa Bay, Bali has made some of the surrounding mangrove ecosystems experience natural damage. The purpose of this study is to determine whether collaboration in planting mangrove seedlings at Mangrove Arboretum Park is good Collaborative Governance. The method used is literature with a qualitative approach. The data sources used are secondary data such as journals, news, and the web. The data findings were then analyzed using the theory of Collaborative Governance by Nasrulhaq (2020) with indicators including consensus orientation, collective leadership, multi-directional communication, and resource sharing. The results of this study explain that every layer of society contributes to the success of a joint action by involving the Balinese government, social communities such as Mangrove Rangers, and civil society such as Balinese students in the mangrove seedling planting movement at Mangrove Arboretum Park, Pedungan, Denpasar. The action and cooperation is a form of Collaborative Governance in overcoming the problem of mangrove forest reclamation in Benoa Bay, Bali.